1989
DOI: 10.1126/science.2665081
|View full text |Cite
|
Sign up to set email alerts
|

The Reservoir for HIV-1 in Human Peripheral Blood Is a T Cell That Maintains Expression of CD4

Abstract: Human immunodeficiency virus type 1 (HIV-1) selectively infects cells expressing the CD4 molecule, resulting in substantial quantitative and qualitative defects in CD4+ T lymphocyte function in patients with acquired immunodeficiency syndrome (AIDS). However, only a very small number of cells in the peripheral blood of HIV-1-infected individuals are expressing virus at any given time. Previous studies have demonstrated that in vitro infection of CD4+ T cells with HIV-1 results in downregulation of CD4 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
285
2
3

Year Published

1991
1991
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 699 publications
(304 citation statements)
references
References 35 publications
14
285
2
3
Order By: Relevance
“…The selective infection and death of CD4+ T cells provides a simple explanation for the impairment of the immune system (2,3). This explanation, however, is widely debated (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…The selective infection and death of CD4+ T cells provides a simple explanation for the impairment of the immune system (2,3). This explanation, however, is widely debated (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…In general agreement with this notion are a number of studies that measured the viral load in serum by quantitative virus culture or quantitative polymerase chain reaction, the number of infected cells in peripheral blood and lymph nodes by PCR or by in situ methods, and the levels of HIV antigenemia by immunologic procedures (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 88%
“…The mechanism by which the virus causes the destruction of the CD4 T cell population is poorly understood, especially as only one in 1000 cells or fewer in peripheral blood are infected with HIV [2]. Other studies have indicated that there is a greater frequency of HIV infection in the lymphoid tissues [3,4], and that the destruction of the CD4 population cannot be attributed to viral load alone.…”
Section: Introductionmentioning
confidence: 99%